Numerical evaluation of the high solidity values effect on the performance of H-Darrieus turbine with NACA 0025 hydroprofiel - Cárdenas, José Daniel Cardona; Marín, Juan Gonzalo Ardila; Toro, Juan José Arbeláez (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study evaluates the performance of high-solidity H-Darrieus hydrokinetic turbines using transient two-dimensional (2D) Computational Fluid Dynamics (CFD) simulations. The objective was to analyze the impact of variations in rotor radius and blade chord length on the mechanical power generated at the shaft and on the power coefficient (Cp). Six rotors with a NACA 0025 airfoil were modeled, covering a solidity range from 1.09 to 1.64. The highest mechanical power generated was 211.6 W with a 450 mm radius rotor at a solidity of 1.09, while the maximum power coefficient (Cp,max) was 0.49. Numerical results demonstrated a strong correlation between the Cp and torque (T) as a function of the tip-speed ratio (TSR). Both magnitudes followed a similar trend, reaching their peaks within an optimal TSR range of 2 and exhibiting analogous behavior throughout the entire performance curve. The findings confirm that for a given solidity, increasing the rotor size significantly enhances the generated torque and power. However, for the solidity values evaluated, an increase in solidity beyond 1.0 has a negative impact on the Cp. Specifically, the rotor with the highest solidity of 1.64 showed a significantly lower maximum power and Cp, in addition to a narrower operational range. The analogous behavior of the Cp trend with respect to solidity variation was corroborated by validation with the experimental findings of Dai and Lam. A discrepancy between the simulation and experimental results of between 31% and 42% was found, which is attributable to the idealizations inherent in the 2D model, such as the omission of three-dimensional effects. Despite these simplifications, the model proved to be a practical and efficient approach for the comparative analysis of turbine geometries in the initial design stages.